Eating Habits and Lifestyles in Schoolchildren from Granada (Spain). A Pilot Study - Gabriel González-Valero; José Luis Ubago-Jiménez; Félix Zurita-Ortega; Ramón Chacón-Cuberos; Manuel Castro-Sánchez; Pilar Puertas-Molero (MDPI AG, 2018)
The creation of healthy habits and lifestyles is fundamental in the educational field and for acquiring adequate health levels that will prevail in adulthood. The aim of this study was to determine the characteristics and correlations between the level of practice of physical activity, adherence to the Mediterranean diet (MD), body mass index (BMI) and problematic use of videogames and self-concept of primary education students. This non-experimental, cross-sectional study is composed of a sample of 577 students aged 10-12 years (11.1 ± 0.638). Subjects were evaluated using the Mediterranean Diet Adherence questionnaire (KIDMED), Self-Concept Form-5 (AF-5), Experiences Related to Videogames (QERV) and anthropometric measurements were taken following the guidelines of the International Society for the Advancement of Kinanthropometry. Most students have been found to be of normal weight, although one in five has problems with being overweight or experiencing obesity. Likewise, half of them need to improve their adherence to the Mediterranean diet, while they do not have a problematic use of videogames, although one tenth of them in these early ages offer severe problems and it is highlighted that students offer an adequate self-concept. It is also noted that BMI correlates positively with problematic videogame use and social self-concept. Greater addiction to videogames is associated with poorer academic performance, low levels of physical activity and poor adherence to the Mediterranean diet. Finally, it should be noted that the continued practice of physical-sports activity favors emotional competence and academic performance.